2014
DOI: 10.1080/08952841.2014.888881
|View full text |Cite
|
Sign up to set email alerts
|

Seeking and Processing Information for Health Decisions among Elderly Chinese Singaporean Women

Abstract: Information behavior includes activities of active information seeking, passive acquisition of information, and information use. Guided by the Elaboration Likelihood Model, this study explored elderly Singaporean women's health information behavior to understand how they sought, evaluated, and used health information in everyday lives. Twenty-two in-depth interviews were conducted with elderly Chinese women aged 61 to 79. Qualitative analysis of the interview data yielded three meta-themes: information-seeking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Buyers of any treatment, including saiga products, were most likely to be middle-aged women. Women’s role in making health decisions for others within their interpersonal network is well documented [41] and as such, our findings confirmed our hypothesis on gender for buyers. A 2006 study found Singaporean wives, more than husbands, were the ones to purchase over-the-counter medicine for their family unit [31].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Buyers of any treatment, including saiga products, were most likely to be middle-aged women. Women’s role in making health decisions for others within their interpersonal network is well documented [41] and as such, our findings confirmed our hypothesis on gender for buyers. A 2006 study found Singaporean wives, more than husbands, were the ones to purchase over-the-counter medicine for their family unit [31].…”
Section: Discussionsupporting
confidence: 90%
“…Regarding motivations for consumption, the highly reported "Someone recommended it to me" answer echoes the well-documented influence of interpersonal communication on human behaviour, including health choices [44]. Specifically within Singapore, Chang et al found that Chinese Singaporean women cited their spouses, parents, and peers as key ongoing influences in their health decisions [41]. The particular impact of familial influence was seen in "Family" being the most reported recommender for saiga product self-usage among our respondents.…”
Section: Discussionmentioning
confidence: 99%
“…The many Facebook shares and personal call‐outs (particularly with identifiably positive responses from targeted individuals), indicates that we achieved our objective of social sharing, thereby socially reinforcing the message. Further, since our target audience looks to their social network for health treatment advice (Chang, Basnyat, & Teo, 2014), even if individuals did not adopt the message directly from our adverts, social reinforcement online or offline by their networks increased the likelihood they would subsequently adopt it.…”
Section: Discussionmentioning
confidence: 99%
“…It is an asset related to health literacy and requires one to access, understand, appraise, and apply health information and services to promote and maintain health [34]. Consistent with a past study conducted in Singapore [35], older adults obtained health information from multiple sources and had to determine such information's trustworthiness. In most situations, older adults reached out to personal social networks for health information, and less frequently via online sources [36].…”
Section: Personal Repositorymentioning
confidence: 93%